2011
DOI: 10.1002/qj.822
|View full text |Cite
|
Sign up to set email alerts
|

The temperature response to stratospheric water vapour changes

Abstract: This study uses an analytical model, based on the cooling-to-space approximation, and a fixed dynamical heating model to investigate the structure of the stratospheric cooling that occurs in response to a uniform increase in stratospheric water vapour (SWV). At all latitudes, the largest cooling occurs in the lower stratosphere and decreases in magnitude with height. The cooling is strongly enhanced in the Extratropics compared to the Tropics. This is markedly different to the case of an increase in CO 2 , whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
68
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 22 publications
5
68
0
Order By: Relevance
“…3d). Increased shortwave heating by higher ozone levels, local tropopause height shifts, and changes in dynamical heating certainly contribute to this, and importantly so does less longwave cooling as a result of the much lower stratospheric water vapour concentrations (Maycock et al, 2011) in G1, as discussed below. The ozone increases in the upper stratosphere are larger in G1 than under 4 × CO 2 (compare Fig.…”
Section: Stratospheric Ozone and Temperature Changesmentioning
confidence: 99%
“…3d). Increased shortwave heating by higher ozone levels, local tropopause height shifts, and changes in dynamical heating certainly contribute to this, and importantly so does less longwave cooling as a result of the much lower stratospheric water vapour concentrations (Maycock et al, 2011) in G1, as discussed below. The ozone increases in the upper stratosphere are larger in G1 than under 4 × CO 2 (compare Fig.…”
Section: Stratospheric Ozone and Temperature Changesmentioning
confidence: 99%
“…To first order, impacts from changes in ozone concentration vary with the total column amount (e.g., surface UV radiation), but other impacts are highly sensitive to changes in the vertical distribution. In particular, several studies have shown a high sensitivity of radiative forcing and local temperature structure from O 3 /WV changes in the upper troposphere and lower stratosphere (UTLS) region (Forster and Shine, 1999;Forster et al, 2007;Maycock et al, 2011;Solomon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Forster and Shine, 2002;Solomon et al, 2010) and also in the effect on the lower stratosphere. For example, Maycock et al (2011) used a set of radiative calculations to show that a uniform increase in stratospheric water vapour gives rise to a cooling that is largest in the lower stratosphere at all latitudes.…”
Section: Introductionmentioning
confidence: 99%